The influence of health education on adolescent behavior regarding consciousness in private health vocational schools Nurul Hashanah Kutacane - Lestari, Fika; Br Tambunan, Yessy Syahradesi (Institute of Computer Science (IOCS), 2024)
Breast cancer is one of the most common cancers in women. The death rate from breast cancer is very high. In 2030, the incidence of deaths from breast cancer will reach 26 million people. The best solution to prevent breast cancer is health education about BSE. The aim of this research is to determine the effect of health education about BSE as an early detection of breast cancer on the knowledge, attitudes and actions of female students at the Nurul Hashanah Kutacane Private Health Vocational School. This type of research is quasi-experimental research, using a pre-test and post-test design method, namely by giving a pre-test (initial observation) first before the intervention is carried out, after the intervention is given, then a post-test (final observation) is carried out. . The research population was 91 class XII female students of the Nurul Hashanah Kutacane Private Health Vocational School and the total sample was 91 female students. The statistical test used was the Wilcoxon test. The results of the paired t-test pre-test and post-test analysis of knowledge obtained a value of p=0.000, which means a value of p<0.05, so it can be concluded that there is an influence of health education about BSE on female students' knowledge. The results of the analysis of the paired t-test pre-test and post-test attitudes obtained a value of p=0.000, which means the value of p> 0.05, so it can be concluded that there is an influence of health education about BSE on the attitudes of female students. With this, it is hoped that the Kutacane Health Service will create a health education work program or a routine schedule for health education and continuously disseminate health information about BSE, especially to schools in Kutacane so that female students know and do BSE so they can detect it early. breast cancer.